1993
DOI: 10.1148/radiology.188.3.8351344
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral sparganosis: MR imaging versus CT features.

Abstract: Fourteen magnetic resonance (MR) images of 11 patients with cerebral sparganosis were reviewed retrospectively and compared with 13 computed tomographic (CT) scans of 10 of the patients. All patients underwent both nonenhanced and contrast material-enhanced MR imaging. All white matter degenerations, which were slightly hypointense on T1-weighted images and were hyperintense on T2-weighted images, were seen as areas of low attenuation on CT scans. Better contrast between normal and degenerated brain tissues wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 0 publications
3
41
1
Order By: Relevance
“…Compared with other studies reported in the literature, 4,5,12,19 the tunnel sign in our study was our first concern because it represented the migration of the worm. Although other imaging findings, such as the bead-shaped enhancement and white matter degeneration, were also reported, our study integrated imaging data, clinical history, and ELISA.…”
Section: Discussioncontrasting
confidence: 44%
See 4 more Smart Citations
“…Compared with other studies reported in the literature, 4,5,12,19 the tunnel sign in our study was our first concern because it represented the migration of the worm. Although other imaging findings, such as the bead-shaped enhancement and white matter degeneration, were also reported, our study integrated imaging data, clinical history, and ELISA.…”
Section: Discussioncontrasting
confidence: 44%
“…The larvae may migrate through the loose connective tissues of the foramina of the skull base around the nerves or vessels. 19 In our study, 12 patients (48%) had a history of eating raw or uncooked frog or snake that was infected with sparganum. They lived in rural areas where the raw flesh of frogs, snakes, or chickens were considered tonic.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations